A versatile Key Management protocol for secure Group and Device-to-Device Communication in the Internet of Things. (15th January 2020) - Kandi, Mohamed Ali; Lakhlef, Hicham; Bouabdallah, Abdelmadjid; Challal, Yacine
Abstract: The Internet of Things (IoT) is a network made up of a large number of devices that collaborate to provide various service for the benefit of society. Two communication modes are required to enable a smooth collaboration. A device can send the same message to several other ones participating in the same service. It may also address a specific device in a Peer-to-Peer manner. The first mode of communication is called Group Communication, while we refer to the second as Device-to-Device Communication. One of the main challenges facing the IoT is how to secure these two modes of communication. Among all the security issues, the Key Management is one of the most challenging. This is mainly due to the fact that most of the IoT devices have limited resources in terms of storage, calculation, communication and energy. Although different approaches have been proposed to deal with this problem, each of them presents its own limitations and weaknesses. Moreover, they usually consider either the Group or the Device-to-Device Communication. In this paper, we propose a novel versatile Key Management protocol for the Internet of Things. To the best of our knowledge, this is the first protocol that secures both modes of communication at the same time. We then analyze the security and performance of our solution and compare it to the existing schemes. For Group Communication, we show that our solution ensures the forward and backward secrecy and, unlike most of the existing Group Key Management protocols, guarantees the secure coexistence of several services in the network. With regard to Device-to-Device Communication, we prove that our solution is flexible and provides a good level of resilience and network connectivity compared to the existing Peer-to-Peer Key Management schemes. We finally demonstrate that, by balancing the loads between the heterogeneous devices according to their capabilities, our solution is both efficient and scalable.